Rozumienie znaczeń związków frazeologicznych w perspektywie uczenia się języków obcych - Sułkowska, Monika (Neofilolog, 2019)
The author of this paper explores the issue of the comprehension of phraseological units. The problem is of great importance not only to linguistics but also to the theory of language learning-teaching as comprehension and phraseological unit acquisition are important factors in the process of teaching any language. The complex semantic structure of phraseological units has resulted in a number of hypotheses which describe the ways in which phraseological units are interpreted. The paper is a review of these hypotheses from a current perspective.